Product profitability assessment - Todić, Vladimir; Bojanić , Ranko (Journal of Production Engineering, 2023)
Product profitability assessment is one of the strategic management tools used in planning and managing product costs, or target profit. Product cost planning and management unfold as early as the development phase, as well as during the adoption of modern production processes. Target profit and product competitiveness on the market require continuous monitoring of market prices, as well as managing costs incurred in the production process. The paper presents the methodology used for product profitability assessment, which is based on the evaluation of product costs and maintaining competitive market prices.